Green self-activation engineering of metal–organic framework derived hollow nitrogen-doped carbon spheres towards supercapacitors. Issue 6 (12th January 2022) - Zhang, Jinyang; Wu, Dongxu; Zhang, Qian; Zhang, Anning; Sun, Jinfeng; Hou, Linrui; Yuan, Changzhou
Abstract : Hollow nitrogen-doped carbon microspheres are fabricated via a green self-activation strategy, and exhibit attractive electrochemical properties for aqueous supercapacitors. Abstract : Recently, hollow carbon spheres have drawn intensive attention towards supercapacitors due to their inherent structural merits. However, the exploration of simple yet efficient activation strategies are always a challenge for scalable synthesis of HCSs but not at the expense of electrochemical properties and environmental issues. Herein, we first devised a green self-activation method to fabricate hollow nitrogen-doped carbon spheres (HNCSs) using hollow zinc metal–organic framework spheres (HZMSs) as the precursor. In this way, in situ N doping both in bulk and on surfaces and hierarchical porosity are realized simultaneously without any additional activators. The underlying formation mechanism of HZMSs is rationally proposed as well. With comprehensive optimization of calcination procedures, the optimized HNCSs are endowed with large contact surface, triple porosity with high-proportion mesopores, suitable N content, and high graphitization, guaranteeing rapid ionic/electronic transport for efficient charge storage on the hydrophilic surface. The resultant HNCS electrodes with a high loading of 5 mg cm −2 exhibit exceptional electrochemical capacitances in aqueous alkaline, acidic and neutral electrolytes in terms of both rate behaviors and stability, which are particularly competitive with and/or better than those of other activated porous carbons. This contribution will guide future design and efficient fabrication of HNCSs towards energy-related applications and beyond.